Cascades of tipping in impacts - Juhola, Sirkku; Rocha, Juan; Sillmann, Jana; Basel, Ashleigh; Constantino, Sara M.; Craparo, Alessandro C. W.; Cumming, Graeme S.; Donges, Jonathan F.; Filatova, Tatiana; Malmström, Alexandra; Mithal, Vidur; Scheffran, Jürgen; et al. (2023)
This chapter advances the state-of-the-art understanding of tipping cascades across scales and systems between Earth system and social tipping points. We consider a tipping cascade to occur when extremes or passing of a tipping point in one system triggers or increases the likelihood of reaching a tipping point in another. Here, this means that crossing an Earth system tipping point or experiencing an extreme volatility in the natural system can lead to cascading impacts that trigger social tipping points, and vice versa.